Study protocol for a randomized trial comparing two electroacupuncture waveforms for different severity groups of Bell palsy - Bian, Zhiyuan; Wang, Jiawei; Fang, Fei; Yu, Binyan; Shi, Yan; Wan, Yijia; Hong, Mei; Ji, Conghua; Shao, Xiaomei; Liang, Yi; Fang, Jianqiao; Sun, Jing (Frontiers in Neurology, 2024)
BackgroundBell palsy (BP) is the most common cause of acute peripheral facial palsy which leads to functional and esthetic disturbances in patients and has a negative influence on daily living. Electroacupuncture (EA) has been considered an alternative treatment for improving facial function in patients with BP. However, there is no agreement on the preferred waveform type of the EA for treating BP.MethodsThis is a study protocol for a pilot randomized, two-arm, three-center, clinical trial at the Third Affiliated hospital of Zhejiang Chinese Medical University, the First Affiliated hospital of Zhejiang Chinese Medical University, and the Hangzhou First People’s Hospital. The trial began in November 2023 and is expected to end in December 2025. Sixty patients with BP whose electroneurography (ENoG) value is at least 20% and 60 patients with BP whose ENoG value is less than 20% will be randomly assigned to the low frequency continuous waveform group or the intermittent waveform group in a 1:1 ratio. Participants will receive 4 weeks of EA treatment and clinical assessments. The primary outcome is the change from baseline score of the Facial Nerve Grading System 2.0. The secondary outcomes include the change from baseline score of the Sunnybrook grading scale and the change from baseline amplitude of the compound muscle action potential of the affected side in the ENoG tests.DiscussionThis is the first study protocol to compare the treatment effect and safety of EA with low frequency continuous waveform and intermittent waveform for different severity groups of BP. This study will contribute to subsequent studies for exploring optimal EA parameters for BP treatment.Clinical trial registrationClinicalTrials.gov, NCT06063954.